Analysis of Challenges and Difficulties in Implementing Information Systems Audit: A Narrative Literature Review - Nurhaflah Soraya; Iskandar Muda; Eliyah A M Sampetoding (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2023)
Information Systems Audit has a main role in the value of any organization from developing countries such as integrity, reliability, security, and privacy. Many researchers are interested in the topic of information systems audit due to the large number of recent business failures. Some research focuses on the current cases from developing countries so this research will give a comprehensive overview of information systems audit. Research gap in the existing literature raised the following research question: What are the difficulties and challenges experienced by developing countries in terms of Information Systems Auditing? The narrative literature review for information systems research was undertaken in line with the theory approach to systematic review. This research analyzed a number of categories that aligned with the grand theories related to difficulties and challenges in the implementation of the Information Systems Audit. In conclusion, this literature review shows that the countries face various challenges and difficulties regarding Information Systems Audit which consists of legislation and policies, culture, education, and human resources.